Development of an electrochemical aptasensor for cocaine detection using CuFe2O4 and electroreduced graphene oxide - Fatemeh Hamdi; Mahmoud Roushani (Sensing and Bio-Sensing Research)
Cocaine is a type of narcotic used for medical purposes, such as local anesthesia in some surgeries. Cocaine diagnosis, which influences health and performance of human beings, is particularly essential in Clinical Toxicology and forensics. This underlines the importance of developing efficient and accurate tools to detect cocaine and track their behavior. Aptamers have been widely used as stable, efficient, and specific biorecognition molecules in biosensors. Herein, a CuFe2O4 (CFO)/ ErGO (Electroreduced graphene oxide) based electrochemical biosensor was fabricated with aptamer for the detection of cocaine. This design increased the active surface area of the electrode that allows more sequences of Apt to be loaded on the surface of the modified electrode. CFO was synthesized using the hydrothermal method. Fe3+ ions are placed on the Cu2+ particles, leading to the production of CFO. Graphene oxide was deposited on it and subsequently reduced through electrochemical means to enhance the electrode surface. In the second step, CFO nanospheres were loaded onto the ErGO-modified electrode surface. The synergy between CFO and ErGO and the porosity of CFO increases conductivity and electron transport. Evaluating the calibration curve showed that the linear range and the detection limit were 0.5 fM- 30 fM and 30 fM- 0.7 nM, and 0.16 fM, respectively. The designed sensor showed excellent selectivity against interfering species. In addition, the performance of this biosensor in human serum samples as an actual sample was appropriately evaluated.